If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + -1) * x + -9(x + -1) = 0 Reorder the terms: -1(-1 + x) * x + -9(x + -1) = 0 Reorder the terms for easier multiplication: -1x(-1 + x) + -9(x + -1) = 0 (-1 * -1x + x * -1x) + -9(x + -1) = 0 (1x + -1x2) + -9(x + -1) = 0 Reorder the terms: 1x + -1x2 + -9(-1 + x) = 0 1x + -1x2 + (-1 * -9 + x * -9) = 0 1x + -1x2 + (9 + -9x) = 0 Reorder the terms: 9 + 1x + -9x + -1x2 = 0 Combine like terms: 1x + -9x = -8x 9 + -8x + -1x2 = 0 Solving 9 + -8x + -1x2 = 0 Solving for variable 'x'. Factor a trinomial. (1 + -1x)(9 + x) = 0Subproblem 1
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Subproblem 2
Set the factor '(9 + x)' equal to zero and attempt to solve: Simplifying 9 + x = 0 Solving 9 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + x = 0 + -9 x = 0 + -9 Combine like terms: 0 + -9 = -9 x = -9 Simplifying x = -9Solution
x = {1, -9}
| -2n+11=5 | | 3n-7=20 | | 8(w-3)=4(3-w) | | X^3-24x=0 | | -2/3t+2-3/4t=-4 | | 2/5x=3/4 | | a^2+50=0 | | q+7-2(q-2)=3(2q+1)+5q | | 1/2x+5+1/3x-5 | | 2a-10=2 | | 13n=42-3 | | 7x+6=9x | | 3x/x-5-5/x-2 | | 13x+195=13(3x+15) | | 4/3z-7+2/3z=-1 | | 88-5x=2x+11 | | -6/x-5-8/x+7 | | 15X+3-7X+4-8X=0 | | 144x^3-258x^2+105x=0 | | pi=3.1416 | | 2x+6/4+5x-2/8 | | 1/2t=-13 | | 7(x-1)=2(2x+4) | | 4x+z=19 | | X+3.5=8.8 | | -x^2-6x+5y^2+10y=22 | | 7(x-5)+14=-7 | | 6x+3=8x-3x | | 12t^2+32t=12 | | 1/2y=1.5 | | 2n/5=30 | | 3z+5z-2=0 |